The Influence of Leadership Style, Motivation, and Work Discipline against Employee Performance in the Regional Secretariat Ogan Komering Ulu (OKU) Regency South Sumatra - Choiriyah, Choiriyah; Djazuli, Abid; Indah, Silvera; Anggeraini, Desi Ulpa; Ulfa, Fithri Atika (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The purpose of this study is to analyze the influence of Leadership Style, Motivation, and Work Discipline against Employee Performance in the Regional Secretariat of Ogan Komering Ulu Regency, South Sumatra.The research design is based on the study environment, the research is included in the field research design category. Researchers focus attention on phenomena in the field so that direct involvement of researchers is limited to observations as cross-information material obtained from the object. The research location was in the Regional Secretariat of Ogan Komering Ulu Regency, South Sumatra, with a total sample of 128 respondents. The analysis technique used: validity and reliability test, multiple linear regression analysis, hypothesis test (F test and t test). The results of the analysis state that there is a significant influence on Leadership Style, Motivation and Work Discipline together against employee performance. And partially significant influence of Leadership Style against Employee Performance. Meanwhile, Work Motivation and Discipline partially do not have significant effects against Employee Performance.